2007
DOI: 10.1016/j.jhealeco.2006.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis prices and dynamics of cannabis use

Abstract: This paper uses duration models and self-reported cannabis histories from young Australians to study the dynamics of cannabis use. We find that low cannabis prices are associated with early initiation into cannabis use. While the decision to quit does not appear to be directly influenced by price, we find that the younger an individual is when they start using cannabis the less likely they are to quit. Therefore, low cannabis prices lead to early use and because of that they lead to a low quit rate and hence a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(28 citation statements)
references
References 28 publications
2
25
0
1
Order By: Relevance
“…“Adults” of course includes parents. Many preventionists hypothesize that legalization of adult non-medical marijuana use will lead to earlier initiation, increased prevalence, and increased frequency of use among youth, even though use remains illegal for them [32-35]. This is because legalization of adult marijuana use may impact several known risk factors for youth marijuana and other drug use, including parent marijuana use and social norms about drug use.…”
Section: Discussionmentioning
confidence: 99%
“…“Adults” of course includes parents. Many preventionists hypothesize that legalization of adult non-medical marijuana use will lead to earlier initiation, increased prevalence, and increased frequency of use among youth, even though use remains illegal for them [32-35]. This is because legalization of adult marijuana use may impact several known risk factors for youth marijuana and other drug use, including parent marijuana use and social norms about drug use.…”
Section: Discussionmentioning
confidence: 99%
“…Van Ours and Williams (2007) and Bretteville-Jensen and Williams (2010) both examined initiation among youth and young adults in Australia and found marijuana price to be negatively associated with initiation. 21,22 In Van Ours and Williams (2007), the initiation elasticity ranged from -0.31 to -0.70, with their preferred specification generating a past year initiation elasticity of -0.50. Bretteville-Jensen and Williams (2010) built on this work and found that initiation was driven by the sample of youth under the age of 18 and the monetary price of marijuana was not statistically significant for predicting initiation of marijuana for individuals after age 18.…”
Section: Discussionmentioning
confidence: 99%
“…The only published work including measures of the monetary price on the decision to quit is the work by van Ours and Williams (2007). 21 In their analysis of young users (under the age of 23) in Australia, they found that the monetary price of marijuana generally had a positive, although statistically insignificant, effect on the likelihood of quitting marijuana in the past year. Considered along with other studies that found that marijuana prices were correlated with the decision to initiate drug use early, 54,55 they suggest their findings suggest that higher marijuana prices still reduce the duration of the typical use career, but they do so by delaying initiation rather than enticing the user to quit.…”
Section: Discussionmentioning
confidence: 99%
“…Economists have formulated models of addiction to study this topic (Becker and Murphy, 1988; Boyer, 1983), and there is a large empirical literature that examines how changes in prices of drugs and incomes of consumers are associated with their consumption (Becker, et al, 1991; Gallet, 2014; Pacula and Lundberg, 2014; Van Ours, 2007; Van Ours and Williams, 2007). The substances that have received the most attention are legal substances, such as nicotine and alcohol, for which product price data are reliable and readily available (Bader et al, 2011; Chaloupka, et al, 2002; Chaloupka, 1999).…”
Section: Introductionmentioning
confidence: 99%